Techno-Economic Analysis of Small-Scale Reverse Osmosis Desalination for Likupang Tourism Area - Maria Anindita Nauli; Harwin; Kezia Rambu Durry (The Indonesian Institute of Science and Technology Research, 2026)
Likupang, a Super Priority Tourism Destination in Indonesia, faces significant challenges in securing a reliable and affordable fresh water supply, currently depending on expensive trucked-in water. This study evaluates the techno-economic feasibility of a small-scale Reverse Osmosis (RO) desalination system to address this issue. Using DuPont’s WAVE Water Treatment Design software, three distinct operational scenarios (A = 50, B = 80, and C = 90 m³/day capacities) were designed and simulated to accommodate the fluctuating water demand characteristic of a tourism area. The technical analysis identified the 80 m³/day demand-responsive scenario as the most energy-efficient, with a Specific Energy Consumption (SEC) of 3.73 kWh/m³. Meanwhile, the economic evaluation, based on the Levelized Cost of Water (LCOW), determined that the most cost-effective strategy is Scenario A with an LCOW of 60,766 IDR/m³. This cost is significantly lower than the current market price of trucked-in water, demonstrating that small-scale RO desalination is a viable and economically competitive solution to support sustainable tourism development in Likupang.